Neutron diffraction study and temperature variation of magnetic anisotropy in Bi substituted nickel ferrite. Issue 16 (15th August 2022) - Bhanu, Vazeera; Madduri, P.V. Prakash; Harsita, M.; Rao, T. Durga; Vinod, K.; Rayaprol, S.; Bhatnagar, A.K.; Mani, Awadhesh; Sattibabu, Bhumireddi
Abstract: Bismuth doped NiFe2 O4 (NFO) polycrystalline samples: Ni1- x Bi x Fe2 O4 with x  = 0.00, 0.05 and 0.10, were synthesized using solid-state reaction method. The crystal structural, magnetic structure and magnetic properties of parent NFO and Bi-doped NFO samples were characterized using X-ray diffraction (XRD), neutron powder diffraction (NPD) and magnetization ( M ) versus magnetic field ( H ) isotherms, respectively. Rietveld refinement of XRD and NPD patterns confirms the formation of a single-phase cubic spinel crystal structure. No observable change in the lattice parameter was found (within the error limits) with the 5 at % Bi doping to NFO, whereas ≈0.15% change in the lattice parameter was observed in case of 10 at % Bi-doped NFO. Room temperature magnetic structure studies using NPD reveal a net magnetic moment of 1.55(3) μB /f. u., in the case of NiFe2 O4 . The net magnetic moment at room temperature changes to 1.61(4) μB /f.u. and 1.47(5) μB /f.u. for Ni0.95 Bi0.05 Fe2 O4 and Ni0.90 Bi0.10 Fe2 O4, respectively. The same observation was also inferred from the spontaneous magnetization ( M sp ) obtained from approach-to-saturation (ATS) analysis of M-H isotherms. Temperature ( T ) dependence of M sp follows a T 2 decline. Approximately 14% increase in magnetic anisotropy was observed in Ni0.95 Bi0.05 Fe2 O4 compared to NiFe2 O4 in the temperature range 5 K -300 K.